Pemanfaatan Search Engine Optimization (SEO) Serta Search Engine Marketing (SEM) untuk Meningkatkan Penjualan Mobil - Meldi Anggara Saputra; Iqbal Fernando; Agus Irawan (Teknik Informatika Fakultas Ilmu Komputer, 2024)
Marketing media for products and services is not only print and electronic media but also internet media. But creating an internet site that is visited a lot is not easy because it requires optimization in searching for the website address. Optimization on websites is better known as SEO (Search Engine Optimization) by applying Site Audit, On Page Optimization and Off Page Optimization as well as SEM (Search Engine Marketing) by applying Search Strategy, Keywords and Site Backlinks as well as Social Media which are important rules so that Internet sites are easier to search. It is proven that in the last three months after using SEO and SEM in October, November to December 2021, there was an increase in web visits by 1027% Unique Visitors, 666% Number Of Visits, 1157% Pages and 3166% Hits and an increase in sales of 38%